2019
DOI: 10.1108/jstp-03-2019-0065
|View full text |Cite
|
Sign up to set email alerts
|

Tough but not terrific: value destruction in men’s health

Abstract: Purpose The purpose of this paper is to investigate the role of masculine identity in generating value destruction and diminished well-being in a preventative health service. Design/methodology/approach This research used five focus groups with 39 Australian men aged between 50 and 74 years. Men’s participation in the National Bowel Cancer Screening Program informed the sample frame. In total, 12 Jungian male archetypes were used to identify different masculine identities. Findings Thematic analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 78 publications
(215 reference statements)
0
4
0
Order By: Relevance
“…In transformative services research literature, there has been preliminary research exploring the relationships between masculinity and health care service provision. For example, McGraw et al (2019) use the perspective of gender identity to explore how there can be several points of contention between services' and men's agendas. For instance, rejecting health services can create positive agency for men (and thus reduce disempowerment and emasculation).…”
Section: Transformative Service Approachmentioning
confidence: 99%
“…In transformative services research literature, there has been preliminary research exploring the relationships between masculinity and health care service provision. For example, McGraw et al (2019) use the perspective of gender identity to explore how there can be several points of contention between services' and men's agendas. For instance, rejecting health services can create positive agency for men (and thus reduce disempowerment and emasculation).…”
Section: Transformative Service Approachmentioning
confidence: 99%
“…A total of 48 papers were included in this review of the literature. A flow chart of the study selection process is reported in Figure 1 11–58 …”
Section: Resultsmentioning
confidence: 99%
“…Research on internal activism could help to understand how employees themselves perceive their role in value co-creation, and what they perceive and accept as value. This could include research on both subtle and overt tactics that employees can use to transform or challenge existing value co-creation processes, how value alignments or misalignments may affect how employees engage in value co-creation (c.f., McGraw et al. , 2019), or how employees work together to maintain or transform value co-creation either across their own organization or across the service system.…”
Section: Opportunities For Social Activism In Transformative Service ...mentioning
confidence: 99%